2015
DOI: 10.1007/s00417-015-3199-4
|View full text |Cite
|
Sign up to set email alerts
|

Severe cranial neuropathies caused by falls from heights in children

Abstract: Cranial neuropathies due to falls from heights are rare in children and are associated with high visual morbidity. Vision or ocular motility impairment, especially monocular vision loss, may be missed during acute intake to the emergency department, and a high index of suspicion is needed. Assessment of the pupillary response to light is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[3,9,20,21] In our series, 45.9% of the falls and 30.8% of the deaths occurred during summer. Al et al [17] and Gulatı et al [3] found that the highest number of falls occurred from 00:00 to 06:00 o'clock.…”
Section: Discussionmentioning
confidence: 50%
“…[3,9,20,21] In our series, 45.9% of the falls and 30.8% of the deaths occurred during summer. Al et al [17] and Gulatı et al [3] found that the highest number of falls occurred from 00:00 to 06:00 o'clock.…”
Section: Discussionmentioning
confidence: 50%
“…In this study, the olfactory, facial, and oculomotor nerves (cranial nerves III, IV, and VI) were most commonly injured and about three out of four CNI patients presented with single nerve palsies which is backed by a vast body of literature [24,26,32,34,42]. Another survey revealed cranial neuropathies affecting visual capacity and/or ocular movement in 1.9% of pediatric inpatient cases hospitalized for severe head trauma resulting from falls [52]. To some extent, investigations from other world regions showed substantially higher CNI prevalences complicating head injuries, ranging between 9.1% and 12.6% for adults and up to 22.4% in children [24,31,34].…”
Section: Discussionmentioning
confidence: 74%
“…2 In children, unilateral CN VI palsies are rare, but bilateral palsies can be related to tumors, elevated intracranial pressure, congenital malformations, postinfectious or postvaccination inflammatory disease, post-lumbar puncture, multiple sclerosis, or genetic syndromes such as Miller Fisher syndrome and Duane retraction syndrome. [3][4][5][6][7][8][9][10][11][12][13] In both children and adults, "nonlocalizing" abducens nerve palsies have also been described, often associated with increased or decreased intracranial pressure. 14 However, Chiari malformation type 1 (CM1) has never been reported to present with isolated abducens nerve palsy in the absence of other symptoms.…”
mentioning
confidence: 99%